Personal Teacher Efficacy and General Teacher Efficacy in Character Education in Reference to Age, Highest Education and Teaching Experience - Sugiana, Sugiana; Formen, Ali (Universitas Negeri Semarang, 2015)
Character development is crucially needed in Indonesia because of continuous moral degradation occurs among Indonesia young generation. It is, however, not and easy for a teacher to accomplish develop character. Teachers and educators, in general, should have solid confidence in order for them to be successful in promoting a good character to their students. Based on this understanding, this study tries to investigate the followings: (1) what is the early childhood teachersâ€™ level of Personal Teacher efficacy (PTE) and general teacher efficacy (GTE) in character education (2) is there any difference early childhood teachers PTE and there GTE in character education with regard to their age, education background, and years of teaching experience. Following a quantitative analysis approach, this study employed descriptive analysis and ANOVA. 115 early childhood teachers based in Kecamatan Gunungpati were involved in this study, the total population of teachers in the Gunungpati was actually 120. However, 5 teachers refused to participate in this study. This study found the followings: (1) would teacher level of Personal teacher efficacy (PTE) and general (GTE) has high in there is and was difference one from another in significantly. (2) In terms of age, highest education, and years of teaching experience there were no significant differences between personal teacher efficacy (PTE) and general teacher efficacy (GTE). Based on these findings, this study suggests(1) further research should be done on a larger or larger subject (2) For further research in order to classify respondents by group category with a distance range that is (3) the research should take into account Indonesian culture which presumably influence teacher self-efficacy(4) enhance teacher professional development(5) for the research should also address early childhood education and professional development specially is aspect of character development.How to citeSugiana, S., & Formen, A. (2015). Personal Teacher Efficacy and General Teacher Efficacy in Character Education in Reference to Age, Highest Education and Teaching Experience.Â Indonesian Journal Of Early Childhood Education Studies, 4(1), 51-56. doi:10.15294/ijeces.v4i1.9454